Tinjauan Ekonomi Syariah Terhadap Penyaluran Dana Modal Usaha Di PNM Mekar Syariah Di Kecamatan Betung Kabupaten Banyuasin - Inge Oktavianti; Eja Armaz Hardi; Agusriandi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
There are many small-scale people who want to have a business to make a living but are still hampered by capital, so they have to look for more loans to build a business that can become a foundation for the continuity of life in the future. With this, the government is now establishing various institutions that are able to increase the income of people who need capital as business capital, one of these institutions is PT. Madani Mekar Syariah National Capital. So the aim of the author's research is to find out how the practice of distributing business capital funds at PT. Madani Mekar Syariah National Capital in Betung District, Banyuasin Regency and also wants to know how sharia economic law applies to combining murabahah and wakalah contracts in one transaction which is applied to PT. Madani Mekar Syariah National Capital in Betung District, Banyuasin Regency. This research uses qualitative methods with respondents, namely branch heads and Account Office members as well as customers. Regarding informants, namely customers who are Muslim, new customers, and have businesses. The results of this research show the flow of fund distribution practices at PT. Mekar Syariah Madani National Capital in Betung District, Banyuasin Regency includes the stage of determining customers according to the criteria set by PNM Mekar Syariah, the second stage is Financing Training, the third stage is signing the agreement and disbursing funds, and the fourth stage is carrying out weekly installments. If we look at sharia economic law regarding the combination of murabahah and wakalah contracts, this is permissible and does not conflict with sharia principles because the murabahah and wakalah financing contracts are carried out at separate times.